Vehicle Gearbox Noise and Vibration : Measurement, Signal Analysis, Signal Processing and Noise Reduction Measures. - Tuma, Jiri (Automotive Series., 2014)
Advances in methods of gear design and the possibility of predicting the sound pressure level and life time of gearboxes and perfect instrumentation of test stands allows for the production of a new generation of quiet transmission units. Current literature on gearbox noise and vibration is usually focused on a particular problem such as gearbox design without a detailed description of measurement methods for noise and vibration testing. Vehicle Gearbox Noise and Vibration: Measurement, Signal Analysis, Signal Processing and Noise Reduction Measures addresses this need and com.